ETIKA PEMERINTAHAN : PERLUKAH ETIKA UNTUK PARTAI POLITIK DAN CALON MENJELANG PEMILU 2024 - , Yoland Prambudi Haryanto; Dewi Noor Azijah; Lolita Deby Mahendra Putri (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Entering a crucial year, the year where a massive democratic party will  be held in Indonesia. In 2024, the democratic party will be for the Indonesian people to be able to determine leaders who are worthy of being leaders and leaders who still use ethics in leading, because there are several leaders who sit and hold office ignoring ethics in leading. Political parties and candidates sell each other’s self-image, increase their electability, and make them the only ones worthy of being elected, however, what needs to be remembered and what people need to instill in their thoughts and feelings is that their voting behavior is what determines the next leader. The method used in ths research is a qualitative method which has an analytical descriptive nature. Data collection was taken through literature studies related to the research in question. The focus of this research will produce argumentative result regarding ethical leaders who can certainly lead, ethics is also found in government itself, where government ethics focuses on legal norms and social norms. In essence, they are public servants and tools in government whose job is to realize the noble ideals of the nation and also to make society prosperous, and not to make their lives and/or the lives of certain groups prosperous.